QLTI-24. ANALYSIS OF DISPARITIES IN PEDIATRIC BRAIN TUMOR BANK ENROLLMENT AS FOUNDATION FOR QUALITY IMPROVEMENT INITIATIVES AT DANA-FARBER CANCER INSTITUTE/BOSTON CHILDREN'S CANCER AND BLOOD DISORDERS CENTER. (14th November 2022) - Tabatneck, Mary; Umaretiya, Puja; Sousa, Cecilia; Vogelzang, Jayne; Ligon, Keith; Baird, Lissa; Cooney, Tabitha
Abstract: BACKGROUND: Tissue biobanks play a vital role in oncology research; however, disparities have been reported in enrollment. The representativeness of biobanks is an important consideration in the extrapolation of research to the broader population. We sought to identify associations between sociodemographic characteristics and pediatric brain tumor bank enrollment at Dana-Farber Cancer Institute and Boston Children's Cancer and Blood Disorders Center (DFCI/BCCBDC) to identify opportunities for improving equitable and representative enrollment. METHODS: We conducted a retrospective cohort study of all patients qualified for enrollment in DFCI/BCCBDC Integrated Tissue and Clinical Data Bank for Patients with Neurological Disorders from 2014-2017 and extracted sociodemographic information from the medical record. The primary outcome was biobank enrollment, and the secondary outcome was approach for enrollment among non-enrolled patients. Exposures of interest included sex, language, interpreter need, race, and ethnicity. RESULTS: We identified 652 eligible patients of which 580 (89%) enrolled and 72 (11%) were non-enrolled. Non-enrolled patients were more likely to be non-English speaking compared to enrolled patients (20% vs 11%; p = 0.0019) and were more likely to require an interpreter (15% vs. 8%; p = 0.025). Non-enrolled patients were more likely to identify as non-white/other/multiple races compared to enrolled patients (29% and 17%; p = 0.0023). Sex and ethnicity were not associated with enrollment. Of the 72 non-enrolled patients, 19 (26%) were approached to discuss enrollment but declined consent. There were no sociodemographic differences between approached and not approached patients. CONCLUSION: While overall enrollment rates in this single center pediatric brain tumor bank were high, non-English primary language, interpreter need, and non-white race were significantly associated with non-enrollment. There were no differences in terms of approach for enrollment, suggesting that opportunities to improve representation may include understanding the reasons for declining enrollment and improving the consent process for patients from historically marginalized groups.